Hexabromocyclododecane flame retardant in Antarctica: Research stations as sources. (November 2015) - Chen, Da; Hale, Robert C.; La Guardia, Mark J.; Luellen, Drew; Kim, Stacy; Geisz, Heidi N.
Abstract: Historical persistent organic pollutants (POPs) are banned from Antarctica under international treaty; but contemporary-use POPs can enter as additives within polymer and textile products. Over their useful lives these products may release additives in-situ. Indeed, we observed 226 and 109 ng/g dry weight (dw) of the total concentrations of α-, β- and γ-hexabromocyclododecane (HBCD) in indoor dust from McMurdo Station (U.S.) and Scott Station (New Zealand), respectively. Sewage sludge collected from wastewater treatment facilities at these stations exhibited ∑HBCD of 45 and 69 ng/g dw, respectively. Contaminants originally within the bases may exit to the local outdoor environment via wastewaters. Near McMurdo, maximum ∑HBCD levels in surficial marine sediments and aquatic biota (invertebrates and fish) were 2350 ng/g (total organic carbon basis) and 554 ng/g lipid weight, respectively. Levels declined with distance from McMurdo. Our results illustrate that Antarctic research stations serve as local HBCD sources to the pristine Antarctic environment. Highlights: HBCD was detected in dust and sewage sludge from Antarctic research stations. HBCD was detected in sediments and organisms in proximity to McMurdo station. Concentrations in sediments or organisms declined with distance from McMurdo. Data reveal research stations serve as HBCD sources to Antarctic environment. Abstract : Evidences from sediments and biota suggest that Antarctic research stations release HBCD to local environment.